The Impact of Learning Strategy by Playing on Multiple Intelligences in Accordance with the Development of Some Basic Football Skills for Students - Hamzah Habeeb, Saad; Suhail Ibrahim, Firas (International Journal of Psychosocial Rehabilitation, 2020)
The learning-by-play strategy aims to develop educational work by developing teaching methods and managing classrooms and knowing their concept and their valuable educational implications in reaching the learner to a good and influential level in learning different mathematical skills, as it makes the student a focus of the educational process and helps him to understand himself and make decisions and invest his energies and help to The growth of his personality is an intellectual, moral, social, and motor development, in addition to the ability to perform the exercises that were established in the memory by building a dynamic program suitable for the learned skill in order to raise his technical and planning level to face the variables of play. The research aims to identify the reality of multiple intelligences, and to identify the impact of the learning strategy by playing according to the multiple intelligences in developing some basic skills of football for students, and the researchers used the descriptive and experimental approach to design the experimental and control groups, and the research sample consisted of first stage students in the College of Physical Education and Science Sports for the academic year 2018-2019 and their number (30) students divided equally into two experimental and control groups, and the researchers prepared a scale of multiple intelligences consisting of (43) paragraphs, and applied the educational units and their number (16) educational units by two educational units In the week, pre- and post-tests were conducted on the scale of multiple intelligences and football skills (passing, extinguishing, and rolling), and the results were extracted through the statistical program (SPSS), and the research came out with conclusions from them that the learning-by-playing strategy contributed greatly to reducing the effort exerted by a teacher in the process of correcting mistakes, providing feedback, and developing technical and skill performance in rolling, passing, and put-down skills.